Point‐of‐care Analysis for Non‐invasive Diagnosis of Oral cancer (PANDORA): A technology‐development proof of concept diagnostic accuracy study of dielectrophoresis in patients with oral squamous cell carcinoma and dysplasia. (12th March 2023) - Hughes, Michael P.; Labeed, Fatima H.; Hoettges, Kai F.; Porter, Stephen; Mercadante, Valeria; Kalavrezos, Nicholas; Liew, Colin; McCaul, James A.; Kulkarni, Raghav; Cymerman, James; Kerawala, Cyrus; Barber, Julie; et al.
Abstract: Background: Delays in the identification and referral of oral cancer remain frequent. An accurate and non‐invasive diagnostic test to be performed in primary care may help identifying oral cancer at an early stage and reduce mortality. Point‐of‐care Analysis for Non‐invasive Diagnosis of Oral cancer (PANDORA) was a proof‐of‐concept prospective diagnostic accuracy study aimed at advancing the development of a dielectrophoresis‐based diagnostic platform for oral squamous cell carcinoma (OSCC) and epithelial dysplasia (OED) using a novel automated DEPtech 3DEP analyser. Methods: The aim of PANDORA was to identify the set‐up of the DEPtech 3DEP analyser associated with the highest diagnostic accuracy in identifying OSCC and OED from non‐invasive brush biopsy samples, as compared to the gold standard test (histopathology). Measures of accuracy included sensitivity, specificity, positive and negative predictive value. Brush biopsies were collected from individuals with histologically proven OSCC and OED, histologically proven benign mucosal disease, and healthy mucosa (standard test), and analysed via dielectrophoresis (index test). Results: 40 individuals with OSCC/OED and 79 with benign oral mucosal disease/healthy mucosa were recruited. Sensitivity and specificity of the index test was 86.8% (95% confidence interval [CI], 71.9%–95.6%) and 83.6% (95% CI, 73.0%–91.2%). Analysing OSCC samples separately led to higher diagnostic accuracy, with 92.0% (95% CI, 74.0%–99.0%) sensitivity and 94.5% (95% CI, 86.6%–98.5%) specificity. Conclusion: The DEPtech 3DEP analyser has the potential to identify OSCC and OED with notable diagnostic accuracy and warrants further investigation as a potential triage test in the primary care setting for patients who may need to progress along the diagnostic pathway and be offered a surgical biopsy.